2016
DOI: 10.1371/journal.pone.0153679
|View full text |Cite|
|
Sign up to set email alerts
|

Turing Patterning Using Gene Circuits with Gas-Induced Degradation of Quorum Sensing Molecules

Abstract: The Turing instability was proposed more than six decades ago as a mechanism leading to spatial patterning, but it has yet to be exploited in a synthetic biology setting. Here we characterize the Turing instability in a specific gene circuit that can be implemented in vitro or in populations of clonal cells producing short-range activator N-Acyl homoserine lactone (AHL) and long-range inhibitor hydrogen peroxide (H2O2) gas. Slowing the production rate of the AHL-degrading enzyme, AiiA, generates stable fixed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…While this system is very similar to the four species model studied in [18], there are some minor differences, but we nevertheless still find that Turing instabilities arise. These differences arise because we arrived at equation (3.14) by reducing a full mass-action system equation (3.13), while the system in [18] is not obtained systematically from a more complex model.…”
Section: Examplessupporting
confidence: 58%
See 3 more Smart Citations
“…While this system is very similar to the four species model studied in [18], there are some minor differences, but we nevertheless still find that Turing instabilities arise. These differences arise because we arrived at equation (3.14) by reducing a full mass-action system equation (3.13), while the system in [18] is not obtained systematically from a more complex model.…”
Section: Examplessupporting
confidence: 58%
“…In [18], it is shown that a model containing five variables (but analysis over four variables due to the presence of a conservation law) can give rise to DDI for certain parameter choices. Already, analysis of Turing instability is made challenging by virtue of there being more than two essential dependent variables.…”
Section: Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, we demonstrated that considering different interconnection structures for different species in reaction-diffusion networks can be leveraged to decrease the often prohibitively large difference in diffusion coefficients required for pattern formation. This result can provide insight when studying self-organization in developmental biology [45] as well as guide the design of population-level behavior in synthetic biology [46]. Additionally, we illustrated not only that random networks with the same density can behave drastically differently in terms of patterning, but more importantly, that this difference can be understood by focusing on the dominant eigenvalue of the interconnection matrix.…”
Section: Discussionmentioning
confidence: 72%